2009
DOI: 10.1111/j.1095-8339.2008.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Type specimens in the Vidal Herbarium at the Real Jardín Botánico, Madrid

Abstract: Ninety eight type specimens collected by Sebastián Vidal in the Philippines, and kept at the Real Jardín Botánico Herbarium, Madrid (MA), are compiled. Most of these specimens are types of Vidal's names. Only a few are names of other authors (Hoogland, Merrill, and Rolfe). A list of specimens, as well as the indicatio locotypica and number in MA, is presented. © 2009 The Linnean Society of London, Botanical Journal of the Linnean Society, 2009, 159, 292–299.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The collections of the Malaspina Expedition include the specimens of Thaddäus Haenke, which are chiefly in Prague and have had a mostly European distribution and only a modest study by Presl (1830) , while the estimated 10,000 collections of Luis Née are presumably still in Madrid and have had almost no distribution or study. Sebastian Vidal’s 14,000 collections from the 1880s are in Madrid ( Calabrese and Velayos, 2009 ), and many are still being studied with important effect. A recent review of Vidal’s collections of Fabaceae found that these century-old specimens included five species not previously documented for the country ( de la Estrella et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The collections of the Malaspina Expedition include the specimens of Thaddäus Haenke, which are chiefly in Prague and have had a mostly European distribution and only a modest study by Presl (1830) , while the estimated 10,000 collections of Luis Née are presumably still in Madrid and have had almost no distribution or study. Sebastian Vidal’s 14,000 collections from the 1880s are in Madrid ( Calabrese and Velayos, 2009 ), and many are still being studied with important effect. A recent review of Vidal’s collections of Fabaceae found that these century-old specimens included five species not previously documented for the country ( de la Estrella et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alberga en tres terrazas escalonadas, plantas de América incluidas las láminas que realizo José Celestino Mutis en la Expedición Botánica . Gracias a las expediciones en Filipinas, el Real Jardín Botánico de Madrid tiene una de las colecciones más importantes de plantas de este país (Calabrese & Velayos, 2009). Además de las grandes colecciones vivas y de láminas del mundo vegetal, en el jardín también se pueden observar muestras de esculturas de científicos destacados tanto a nivel de la península ibérica como de otras partes del mundo.…”
Section: Real Jardín Botánico De Madrid (España)unclassified
“…He renumbered Vidal's specimens, apparently giving the same number to all sheets belonging to the same species, without taking in consideration the localities and dates of each collection. This procedure brought additional difficulties in the recognition of the material (Calabrese and Velayos 2007). However, the numbers included by Quisumbing have been used by different authors as if they were Vidal's numbers.…”
mentioning
confidence: 99%